Global protein sustainability and the United Nations, through to the 2030 agenda - Burlingame, Barbara; Moltedo, Ana; Cafiero, Carlo (Frontiers in Nutrition, 2024)
Organizations and initiatives concerned with food security and nutrition have long positioned protein, together with dietary energy, as the keystone for life itself. Indeed, the word protein, derived from the Greek proteios, means ‘of primary importance’. There is a long history of attention to, and controversies over, proteins in UN processes, beginning in the 1930s and continuing to this day. The importance of protein for agriculture, health, food security and nutrition is reflected in the data collected and presented in the statistical databases of the Food and Agriculture Organization (FAOSTAT), available per commodity, per country and over an extensive time series. Protein features directly and indirectly in all 17 Sustainable Development Goals (SDG), which constitute the United Nations 2030 Agenda. Most directly involved is SDG 2. The short title for SDG 2 is ‘zero hunger’. The long title offers more detail: end hunger, achieve food security and improved nutrition and promote sustainable agriculture.